COVID-19 vaccination knowledge, attitudes and practices among residents of Bosnia and Herzegovina during the third wave of COVID-19 outbreak - Šljivo, A.; Ćetković, A.; Abdulkhaliq, A.; Kiseljaković, M.; Selimović, A.; Kulo, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Bosnia and Herzegovina hasn’t still developed and started any vaccination programs to contain the current COVID-19 outbreak and prevent further spreading and death from this disease. The aim of this study was to assess current knowledge, attitudes and practices towards COVID-19 vaccination during the third wave of the outbreak when the healthcare system is facing a collapse and to create a paradigm for developing vaccination programs in the country.Methods. This cross-sectional study was conducted by an anonymous online questionnaire based on a Congo study and Center for Disease Control and Prevention facts regarding COVID-19 vaccination during the third wave of the COVID-19 outbreak in the country.Results. In total, 570 subjects, mostly female 474 (83.1%), with a high school degree or lower 230 (40.3%), married 305 (53.5%), engaged in intellectual labor 302 (53.0%), from urban environment 531 (93.1%) and with a mean age of 35.28±11.35, were included in the study. The mean COVID-19 vaccination knowledge test score was 11.29±1.91. Being single (OR= 1.88, 95% 1.20-2.94) or in a relationship (OR=1.87, 95% 1.12-3.11), being engaged in intellectual labor (OR=1.59, 95% CI 1.06-2.37) and having a Master’s degree or higher (OR=1.65, 95% CI 1.10-2.46) were associated with higher knowledge test scores. Only 264 (46.3%) subjects agreed that COVID-19 vaccination programs will prevail in a battle versus COVID-19 and only 36 (6.3%) were currently vaccinated against COVID-19. Higher knowledge regarding COVID-19 and its vaccination was determined as an independent predictor for vaccinating itself against COVID-19 (OR=23.09, 95% CI 11.94-44.68), as well as respecting socio-epidemiological measures such as avoidance of crowded places (OR=2.07, 95% CI 1.28-3.35) and wearing face mask (OR=6.95, 95% CI 2.07-23.29).Conclusions. Our study shows that Bosnia and Herzegovina population has poor knowledge, relatively pessimistic attitudes and a very low vaccinal rate against COVID-19 during the third wave of the outbreak which promotes COVID-19 vaccination hesitancy and further COVID-19 spreading and death toll. By activating proper socioepidemiological measures and educating population about COVID-19 and COVID19 vaccination, as well as vaccination against COVID-19, the current situation could be changed.